The mask of mirrors eaudiobook - Carrick, M. A. (Rook & Rose Series., 2021)
The Mask of Mirrors is the unmissable start to the Rook & Rose trilogy, a darkly magical fantasy adventure in which a con artist returns to the city that betrayed her, determined to have her revenge—only to find that her fate might be to save it. This is your past, the good and the ill of it, and that which is neither. Arenza Lenskaya is a liar and a thief, a pattern-reader and a daughter of no clan. Raised in the slums of Nadezra, she fled that world to save her sister. This is your present, the good and the ill of it, and that which is neither. Renata Viraudax is a con artist recently arrived in Nadezra. She has one goal: to trick her way into a noble house and secure her fortune. This is your future, the good and the ill of it, and that which is neither. As corrupt nightmare magic begins to weave its way through the City of Dreams, the poisonous feuds of its aristocrats and the shadowy dangers of its impoverished underbelly become tangled-with Ren at their heart. And if she cannot sort the truth from the lies, it will mean the destruction of all her worlds.